Handbook of research on communication strategies for taboo topics - Luurs, Geoffrey, 1987- (Advances in linguistics and communication studies (ALCS) book series., 2022)
"This book provide in-depth coverage of the broad range of taboo topics, concepts related to taboo, intercultural perspectives on taboo, and principles for interdisciplinary perspectives on taboo including communication research on taboo that includes a range of methods, strategies, and viewpoints on the value of taboo and topic avoidance"--